THE EFFECTS OF PROPOLIS MOUTHWASH ON INCREASING THE pH OF SALIVA IN PERSATUAN AMAN BAKTI (PAB) 12 SAMPALI ELEMENTARY SCHOOL - Ika Devi Adiana; Tri Suci Alfarani (FKG ULM, 2025)
Background: The main problem in dental and oral health among children is dental caries, a complex disease that begins with acid production that destroys dental minerals. When the pH drops to below 5,5, demineralization occurs faster than remineralization, potentially causing cavities. One approach to addressing this issue is by increasing salivary pH. Purpose: This study aims to determine the effect of gargling with propolis mouthwash on increasing salivary pH among children aged 7-9 years. Methods: This laboratory experimental study used a pretest-posttest controlled-group design. A total of 40 respondents from PAB 12 Sampali Elementary School were selected through purposive sampling. Salivary samples (5 ml) were collected and pH levels measured using a pH meter. Results: The Wilcoxon test showed that the average salivary pH before using propolis mouthwash was 6.39, increasing to 7.07 after use. There was a significant effect of propolis mouthwash on salivary pH (p-value = 0.000). Conclusion: The findings indicate that propolis mouthwash effectively increases salivary pH in children aged 7–9 years.